2019
DOI: 10.3390/nu11081745
|View full text |Cite
|
Sign up to set email alerts
|

The Baseline Nutritional Status Predicts Long-Term Mortality in Patients Undergoing Endovascular Therapy

Abstract: Introduction: Peripheral artery disease (PAD) occurs at an advanced stage of atherosclerosis and its comorbidities are associated with poor prognoses. Malnutrition is related to the severity of atherosclerosis in patients with cardiovascular disease and it predicts mortality. The Controlling Nutritional Status (CONUT) score is calculated from serum albumin concentration, peripheral lymphocyte count and total cholesterol concentration, and it robustly represents the nutritional status of hospitalized patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 43 publications
2
21
0
1
Order By: Relevance
“…Newer principles of multidisciplinary care have been applied to patients with CLTI, and additional treatments such as hyperbaric oxygen therapy, lipoprotein apheresis, and nutritional interventions were started later in this study. 28,29 This additional care has the potential to influence the results, which need confirmation in larger studies.…”
Section: Discussionmentioning
confidence: 99%
“…Newer principles of multidisciplinary care have been applied to patients with CLTI, and additional treatments such as hyperbaric oxygen therapy, lipoprotein apheresis, and nutritional interventions were started later in this study. 28,29 This additional care has the potential to influence the results, which need confirmation in larger studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have described the use of nutritional indices calculated using multiple parameters to predict both early and longer-term outcomes in patients with PAD. 17 However, to the best of our knowledge, there have been no studies of the relationship between preoperative nutritional status assessed using a nutritional index and WH. Therefore, we believe that this is the first study to show a positive relationship between these parameters in patients with tissue loss.…”
Section: Discussionmentioning
confidence: 99%
“…2 showed that GNRI is independently associated with all-cause mortality in patients with CLI undergoing EVT, and Mizobuchi et al. 5 showed that a CONUT score ≥ 5 is an independent predictor of three-year OS in patients with PAD undergoing EVT. Mii et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study demonstrated that good nutritional status is an independent predictor of better clinical outcomes in patients undergoing EVT. 26) However, there are currently no recommendations for underweight PAD patients to gain weight in order to improve clinical outcomes. Further studies are needed to elucidate the role of increasing muscle, nutritional support, and weight gain on prognosis of PAD in underweight patients.…”
Section: Discussionmentioning
confidence: 99%